Correlation between serum ferritin, serum iron and blood glucose level in patients of type 2 diabetes mellitus - Khadiza, B; Farjana, A; Murshida, A; Fahmida, L; Tahiya, T (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Ferritin is a ubiquitous intracellular protein complex that reflects the iron stores of the body. Many cross-sectional studies indicate that increased body iron stores have been associated with the development of glucose intolerance, type 2 diabetes,metabolic syndrome. This study was carried out to find out the relationship between serum ferritin, serum iron and type 2 diabetes and to see the influence of body iron storesand blood glucose. Methods: This study includes 81 patients suffering from type 2 diabetes and compared with controls at BIRDEM General Hospital. Serumferritin serum iron andFasting Blood Sugar (FBS) were measured. Results: Serum ferritin was significantly higher (p<0.0001) in the patients suffering from type 2 diabetes. The levels of serum ferritin were positively correlated with values of FBS. Conclusions: There is a positive association between elevated iron stores measured by serum ferritin levels, serum iron and type 2 diabetes mellitus. Theassociation of age category of study groups with serum ferritin were also seen. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 15-17